Spatial localization of PtdInsP2 in phase-separated giant unilamellar vesicles with a fluorescent PLC-delta 1 PH domain - Mulet,X; Rosivatz,E; Ho,KK; Gauthe,BL; Ces,O; Templer,RH; Woscholski,R (Methods Mol.Biol., 2009)
This chapter describes a method for the preparation of giant unilamellar vesicles containing phosphatidylinositol 4,5-bisphosphate that are larger than 20 microm in size. The phospholipids composition of the vesicular membrane is such that fluid lamellar and liquid-ordered or gel phases are formed and separate within the confines of one vesicle. It outlines the preparation of a protein fluorescent label, pleckstrin homology domain from phospholipase C-delta 1, that binds specifically to phosphatidylinositol 4,5-bisphosphate. Using fluorescence microscopy, the presence and spatial position of this phosphorylated phosphatidylinositol lipid on the lipid membrane have been located with the pleckstrin homology domain. We show that phosphatidylinositol 4,5-bisphosphate and the phospholipase C-delta 1 pleckstrin homology domain are located to the fluid phase of the vesicle membrane. This approach can therefore show how membrane physical properties can affect enzyme binding to phosphatidylinositol 4,5-bisphosphate and thus further the understanding of important membrane processes such as endocytosis